Explanation and progress in security studies bridging theoretical divides in international relations - Chernoff, Fred (Stanford University Press, 2014)
Explanation and Progress in Security Studies asks why Security Studies, as a central area of International Relations, has not experienced scientific progress in the way natural sciences have-and answers by arguing that the underlying reason is that scholars in Security Studies have advanced a range of different notions of "explanation" or different criteria of "explanatory superiority" to show that their positions are better than rival positions. The book reveals that authors in the debates that have shown the most progress use similar criteria in arguing for and against the key explanations.